Palestine and Israel Conflict: Disagreement Strategies on Social Media X Discussion - Purnawati, Purnawati; Anwar, Miftahulkhairah; Rohman, Saifur (Foremost Journal, 2025)
Nowadays, social media has become a profound place for people to express their opinion and ideas, one of them is X social media (formerly known as Twitter). This study analysed how people expressed their opinion specifically on their disagreement strategies in X post. Thus, the focus of this research is to examine the types of disagreement found in the X corpus based on the linguistic used. There are 176 tweets taken from disagreement comments on 4 postings about recent Palestine and Israel conflicts. It was analysed manually by codifying on the types of disagreement. The finding revealed that the major type of disagreement is mitigating disagreement reaching 65%. While 10% of unmitigated disagreements expressions were categorized as aggravated. Furthermore, there were found types of employed mitigated disagreement including: Adding support (43%), Sarcasm (25%), Indirect (23%), Modulation (5%), and Delay (3%). The finding showed that people on social media tend to mitigate their disagreements using explanation and sarcasm. The mildest way to convey disagreements gained the least numbers of frequency. Therefore, it can be said that people in social media tend to openly express their disagreements by strong statements. This research can be a reference on how people digitally interact in social media.